A multi-biomarker approach for the early assessment of the toxicity of hospital wastewater using the freshwater organism Daphnia magna - Afsa, Sabrine (2022)
Hospital wastewater (HWW) contains different hazardous substances resulting from a combination of medical and non-medical activities of hospitals, including pharmaceutical residues. These substances may represent a threat to the aquatic environment if they do not follow specific treatment processes. Therefore, we aimed to investigate the effects of the untreated effluent collected from a general hospital in Mahdia City (Tunisia) on neonatal stages of the freshwater crustacean Daphnia magna. Test organisms were exposed to three proportions (3.12%, 6.25%, and 12.5% v/v) of HWW. After 48 h of exposure, a battery of biomarkers was measured, including the quantification of antioxidant enzymes [catalase (CAT) and total and selenium-dependent glutathione peroxidase (total GPx; Se-GPx)], phase II biotransformation isoenzymes glutathione-S-transferases (GSTs), cyclooxygenases (COX) involved in the regulation of the inflammatory process, and total cholinesterases (ChEs) activities. Lipid peroxidation (LPO) was measured to estimate oxidative damage. The here-obtained results showed significant decreases of CAT and GSTs activities and also on LPO content in daphnids, whereas Se-GPx activity was significantly increased in a dose-dependent manner. Impairment of cholinesterasic and COX activities were also observed, with a significant decrease of ChEs and an increase of COX enzymatic activities. Considering these findings, HWW was capable of inducing an imbalance of the antioxidant defense system, but without resulting in oxidative damage in test organisms, suggesting that peroxidases and alternative detoxifying pathways were able to prevent the oxidant potential of several drugs, which were found in the tested effluents. In general, this study demonstrated the toxicity of hospital effluents, measured in terms of the potential impairment of key pathways, namely neurotransmission, antioxidant defense, and inflammatory homeostasis of crustaceans.